FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PELAKSANAAN PELAYANAN PRIMA PEGAWAI DI RSUI ORPEHA TULUNGAGUNG - Muhammad Ali Sodik; Sentot Imam Suprapto; Dian Pangesti (STRADA : Jurnal Ilmiah Kesehatan, 2013)
The hospital has a primary function to serve the people who need health care , so hospitals should prepare for the demands of the people to obtain optimal health care by providing excellent service . The purpose of this study was to determine what factors are associated with the implementation of excellent service employees in RSUI ORPEHA Tulungagung. Design this was an observational study with cross-sectional, with a population of all existing employees in RSUI ORPEHA Tulungagung totaling 195 people. The sample is part of a population that met the inclusion criteria a number of 70 respondents. Techniques of data collection using questionnaires and observation using a checklist of excellent service implementation. Collected data is processed with statistical logistic regression with significance α < 0.05. Based on the results of logistic regression statistical tests showed that the leadership factor (p = 0.001), factor employment status (p = 0.016) and motivational factors (p = 0.000) were factors associated with the implementation of the excellent service at the Islamic Hospital Tulungagung. Note also that the factor of employment status is the most dominant factor associated with excellent service with a value of p = 0.021 and odds ratio of 59.7. The results of this study concluded the need for increased efforts management with all parties concerned, especially with regard to employment status factor, leadership and motivation to further improve the excellent service at the Islamic Hospital Tulungagung.